Risk Management Interventions to Reduce Injuries and Maximize Economic Benefits in U.S. Mining. Issue 3 (March 2018) - Griffin, Stephanie C.; Bui, David P.; Gowrisankaran, Gautam; Lutz, Eric A.; He, Charles; Hu, Chengcheng; Burgess, Jefferey L.
Abstract : Objective: Risk management (RM) is a cyclical process of identifying and ranking risks, implementing controls, and evaluating their effectiveness. This study aims to identify effective RM interventions in the U.S. mining industry. Methods: RM interventions were identified in four companies representing metal, aggregate, and coal mining sectors. Injury rates were determined using Mine Safety and Health Administration (MSHA) data and changes in injury rates identified through change point analysis. Program implementation costs and associated changes in injury costs were evaluated for select interventions. Results: Six of 20 RM interventions were associated with a decline in all injuries and one with a reduction in lost-time injuries, all with a positive return on investment. Conclusion: Reductions in injuries and associated costs were observed following implementation of a limited number of specific RM interventions.